2013
DOI: 10.3389/fonc.2013.00226
|View full text |Cite
|
Sign up to set email alerts
|

Cabazitaxel-Induced Stabilization of Microtubules Enhances Radiosensitivity in Ovarian Cancer Cells

Abstract: Background: Up to 40% of women with ovarian cancer have short disease-free intervals due to molecular mechanisms of chemotherapy resistance. New therapeutic strategies are sought. Ovarian cancers are sensitive to radiochemotherapy. The taxane cabazitaxel (XRP6258, Jevtana) promotes tubulin assembly and stabilizes microtubules against depolymerization in cells, acting similarly in mechanism to paclitaxel. Here, sequences of cabazitaxel-radiation co-administration are tested for drug-alone cytotoxicity and optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Therefore, the results showed that well‐tolerated doses of Cabazitaxel followed by radiation administration against U87MG cells will exert profound alteration of radiation response and bring about cell growth suppression. The result of the present study is in line with the study of Kunos et al (Kunos et al, ). These authors evaluated the radiosensitizing effect of Cabazitaxel in ovarian cancer cells.…”
Section: Resultssupporting
confidence: 94%
“…Therefore, the results showed that well‐tolerated doses of Cabazitaxel followed by radiation administration against U87MG cells will exert profound alteration of radiation response and bring about cell growth suppression. The result of the present study is in line with the study of Kunos et al (Kunos et al, ). These authors evaluated the radiosensitizing effect of Cabazitaxel in ovarian cancer cells.…”
Section: Resultssupporting
confidence: 94%
“…30,31 PTX-mediated radiosensitization is caused mainly by the stabilization of microtubules as a result of enhanced tubulin polymerization that leads to an accumulation of cells in the G2/M phase of cell cycle, which are known to be radiosensitive. 32 Second, the NDs combined ultrasound irradiation can mechanically perturb cell membranes, dysregulate biochemical signaling pathways of cell apoptosis, and additionally initiate tumor cell injury and lysis directly. 33,34 Early studies have discovered that the interaction of ultrasound with tissue can induce mechanical effects, chemical effects and thermal effects.…”
Section: Discussionmentioning
confidence: 99%